2020
DOI: 10.3389/fgene.2020.569232
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Programming Through Breast Milk and Its Impact on Milk-Siblings Mating

Abstract: Background The epigenetic effects of transmission of certain regulatory molecules, such as miRNAs, through maternal milk on future generations, are still unknown and have not been fully understood yet. We hypothesized that breastfeeding regularly by adoptive-mother may cause transmission of miRNAs as epigenetic regulating factors to the infant, and the marriage of milk-siblings may cause various pathologies in the future generations. Results A cross-fostering model usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…A total of 829 genes were differently expressed on P10 between saline and MIA milk samples ( Figure 3A ). We analyzed clusters of gene networks that are involved in maternal milk nutrition, immune activation, and offspring brain development (Quintana et al, 2019; Oakley & Cidlowski, 2013; Polman et al, 2012; Zhu et al, 2016; Ozkan et al, 2020; Zhang et al, 2013; Bowen et al, 2013; Borish & Steinke, 2003; Figure 3B). Heatmap clustering revealed a general upregulation of genes related to nutrient transport and inflammation, while genes related to epigenetic modifications, parvalbumin interneuron development, and glucocorticoid signaling were largely downregulated by MIA on P10 ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 829 genes were differently expressed on P10 between saline and MIA milk samples ( Figure 3A ). We analyzed clusters of gene networks that are involved in maternal milk nutrition, immune activation, and offspring brain development (Quintana et al, 2019; Oakley & Cidlowski, 2013; Polman et al, 2012; Zhu et al, 2016; Ozkan et al, 2020; Zhang et al, 2013; Bowen et al, 2013; Borish & Steinke, 2003; Figure 3B). Heatmap clustering revealed a general upregulation of genes related to nutrient transport and inflammation, while genes related to epigenetic modifications, parvalbumin interneuron development, and glucocorticoid signaling were largely downregulated by MIA on P10 ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…RNA-seq revealed several differently expressed genes involved with milk triglyceride and nutrient transport downregulated by EE, including Ghr (p = .024, FC = −0.671), Igf1 (p = 0.03, FC = −0.671), Slc27a4 (p= 0.032, FC = −0.447), Gpat4 (p<.001, FC = −0.613), and Cs1s2b (p = 0.009, FC = −0.838; Velmala et al, 1995; Figure 3B, C ). We broadened the scope of our analyses further to include gene pathways related to oxytocin (Quintana et al, 2019), glucocorticoid receptor (GR) signaling (e.g., events that occur when glucocorticoids bind to the GR receptor; (Oakley & Cidlowski, 2013), GR binding (e.g., genes which bind the glucocorticoid receptor; Polman et al, 2012), and epigenetic modifiers (Zhu et al, 2016; Figure 3D, E, F, G ) given their crucial implication in milk production and offspring development (Ozkan et al, 2020; Zhang et al, 2013). Heatmap clustering showed that EE rats displayed a major downregulation of genes encoding for triglycerides and nutrient transport (Figure 3B, C) , while genes related to oxytocin and GR (Figure 3D, E) signaling were mostly upregulated compared to SD rats.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence supports the concept that milk functions as an epigenetic modifier suppressing the activity of DNA methyltransferase 1 (DNMT1) [ 107 , 108 , 109 , 110 , 111 , 112 ]. Fresh and pasteurized cow’s milk transfers bioactive milk exosomes (MEX) (50–100 nm in diameter) to the milk recipient [ 113 , 114 , 115 , 116 , 117 ].…”
Section: Milk: a Signaling System For Postnatal Growth And Differementioning
confidence: 99%